Time Perception Deficits in Children and Adolescents with ADHD: A Meta-analysis. Issue 2 (January 2022) - Zheng, Que; Wang, Xinyue; Chiu, Ka Yu; Shum, Kathy Kar-man
Objective: Prior studies have reported time perception impairment in children and adolescents with ADHD but the results were inconsistent. Method: The current meta-analysis reviews 27 empirical studies published in English after year 2000 that compared time perception competence among children and adolescents with and without ADHD. Results: Results from 1620 participants with ADHD and 1249 healthy controls showed significant timing deficits in ADHD. Children/adolescents with ADHD perceived time less accurately (Hedges' g  > 0.40), less precisely (Hedges' g  = 0.66) and had higher tendency to overestimate time than their healthy counterparts. Moderator analyses indicated that the discrepancy of time perception between groups was not affected by the type of timing tasks nor the modality of stimuli used in the tasks. Nonetheless, results were moderated by age and gender. Conclusion: These findings may update current understanding of the underlying neuropsychological deficits in ADHD and provide insight for future research in clinical assessments and treatments for ADHD.